EFFECT OF ALGINAT CONCENTRATION VARIATION AND LIPASE CONCENTRATION TO HYDROLYSIS ACTIVITY AND SPECIFIC ACTIVITY OF AMPILE LIPASE IN LIPASE AMOBILIZATION PROCESS FROM Rhizopus delemar - Nani Ratnaningsih (Jurnal Penelitian Saintek, 2004)
Effect of lipasefrom Rhizopus delemar and alginate concentration during immobilization preparation  on the hydrolytic  activity  and the specific activity of immobilized lipase has been studied  Immobilization of lipase was done by entrapping lipase onto Ca-ulginate beads with 0.2 M CaC/] Immobilized lipase made from   9  variations  bv mixing lipase at same weight with  1%.2   % and 3 % (VI'IV)  alginate solution concentration and10 11'1210,ml and 30 ml alginate volume. The stability of   immobilizedlipase  activity for   repeated  used  reactions  were  also  observed   The selected immobilized Iipasefromfirst  step wasfree:e  driedfor  24, 36 and48 hours. Both the hydrolytic activitv and the specific activity of immobilized lipase were affected hv lipase and alginate concentration. The hydrolytic activity  of immobilized lipase decreased with the reduction of lipase concentration, however. the specific activity increased accordingly. After  freeze  drying, the activity of immobilized lipase was also affected by alginate and lipase concentration. The activity of immobilized liposes were stabil, however, increased  afterfreeze drying.